Sistem Pendukung Keputusan Penerimaan Karyawan Menggunakan Metode MFEP - hia, Meriani; Rohman, Abdul (Jurnal Algoritma, 2025)
The employee recruitment process is a crucial stage in determining the quality of human resources in a company. Decision-making that relies solely on intuition or subjective judgment often leads to inaccuracies in selecting the best candidates. This study aims to develop an employee recruitment decision support system using the Multi Factor Evaluation Process (MFEP) method to provide objective and measurable assessment results. The MFEP method was chosen for its ability to evaluate alternatives based on a number of predetermined criteria. The criteria used in this study included education, work experience, technical skills, communication skills, and interview results. Each criterion was weighted based on its level of importance, then normalized and calculated to determine the total score for each candidate. The results of the system implementation show that the MFEP method is able to assist decision makers in assessing and determining the most suitable candidates efficiently and systematically. This system also minimizes subjectivities in the selection process and increases transparency and accountability in the assessment of new employees. Thus, the application of the MFEP method in decision support systems can be an effective solution in improving the quality of recruitment in companies.